Solid electrolytic capacitor element and solid electrolytic capacitor
By using the first metal particles containing silver to replace the copper particles, a highly conductive metal-containing particle layer is formed, and the problem of increased leakage current of solid electrolytic capacitors at high temperatures is solved, and cost reduction and reliability improvement are achieved.
Patent Information
- Application Number
- CN202380067431.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-07-18
- Publication Date
- 2025-04-25
AI Technical Summary
After the solid electrolytic capacitor is exposed at high temperature, the metal-containing particle layer of copper particles will cause a significant increase in leakage current, resulting in an increase in the short circuit failure rate.
A first metal particle containing silver is used, which consists of silica core particles and a silver cover layer to replace the copper particles to form a highly conductive metal-containing particle layer.
It effectively reduces the manufacturing cost of solid electrolytic capacitors, and significantly reduces leakage current at high temperatures, reduces short-circuit defect rate, and improves the moisture resistance and reliability of the capacitor.
Smart Images

Figure CN119895520A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolytic capacitor element and a solid electrolytic capacitor. Background Art
[0002] The solid electrolytic capacitor comprises: a solid electrolytic capacitor element, an outer shell that seals the solid electrolytic capacitor element, and an external electrode electrically connected to the solid electrolytic capacitor element. The solid electrolytic capacitor element comprises: an anode body, a dielectric layer formed on the surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer. The cathode portion comprises, for example, a solid electrolyte layer containing a conductive polymer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer. The cathode lead layer comprises, for example, a carbon layer covering at least a portion of the solid electrolyte layer, and a metal particle-containing layer covering at least a portion of the carbon layer. The cathode lead layer is electrically connected to the external electrode on the cathode side via a cathode lead.
[0003] The metal particle-containing layer is often formed using a conductive paste containing silver particles and a resin binder from the viewpoint of ensuring high conductivity, but there are disadvantages such as high cost due to the high cost of silver particles.
[0004] A proposal has been proposed to use copper particles instead of silver particles in the metal particle-containing layer. For example, Patent Document 1 proposes a tantalum solid electrolytic capacitor that uses a sintered body formed of fine powder of a valve-acting metal, on which an oxide coating layer, a manganese dioxide layer, and a conductive layer formed of fine powder of carbon are sequentially formed, and a conductive paste containing copper powder is formed thereon.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 4-85915 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] Solid electrolytic capacitors are usually soldered to a substrate through a reflow process exposed to high temperatures. Using copper particles instead of silver particles in the conductive paste used in the cathode can reduce costs, but in solid electrolytic capacitors having a solid electrolyte layer containing a conductive polymer, leakage current increases significantly after exposure to high temperatures.
[0010] Solutions for solving problems
[0011] A first aspect of the present disclosure relates to a solid electrolytic capacitor element, comprising: an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer.
[0012] The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer, and at least a portion of the cathode portion includes a metal particle-containing layer.
[0013] The solid electrolyte layer comprises a conductive polymer.
[0014] The metal particles contained in the metal particle-containing layer include first metal particles containing silver.
[0015] The first metal particles include: a core particle containing silicon dioxide, and a silver-containing covering layer covering the core particle.
[0016] A second aspect of the present disclosure relates to a solid electrolytic capacitor including: at least one solid electrolytic capacitor element as described above; and an outer case that seals the solid electrolytic capacitor element.
[0017] Effects of the Invention
[0018] The manufacturing cost of the solid electrolytic capacitor can be reduced, and the leakage current after exposure to high temperature can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 1 is a schematic cross-sectional view of a solid electrolytic capacitor according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0020] The novel features of the present invention are described in the appended claims, but the present invention, both about the configuration and content, together with other objects and features of the present invention, should be further fully understood from the following detailed description with reference to the accompanying drawings.
[0021] The metal particles used in the metal particle-containing layer constituting a part of the cathode portion of the solid electrolytic capacitor are required to have high electrical conductivity. The content of the metal particles in the metal particle-containing layer is relatively high (e.g., 80% by mass or more). Therefore, if copper particles or the like are used as highly conductive metal particles instead of silver particles, it is expected that the cost can be greatly reduced.
[0022] Solid electrolytic capacitors are usually soldered to the substrate through a reflow process exposed to high temperature. In addition, solid electrolytic capacitors are also used in high temperature environments depending on the application. In solid electrolytic capacitors, when copper particles are used in the metal particle-containing layer, even if the initial leakage current is small, the leakage current sometimes increases after the solid electrolytic capacitor is exposed to high temperature. In addition, due to the large leakage current, a short circuit occurs, and sometimes the defective rate of the product (hereinafter sometimes referred to as the short circuit defective rate) increases.
[0023] In a solid electrolytic capacitor having a metal particle-containing layer containing copper particles, the increase in leakage current after exposure to high temperature is believed to be based on the following reasons. If the solid electrolytic capacitor is exposed to high temperature, the copper particles that are more easily ionized than silver particles are ionized due to the action of heat or the action of gas generated by the polymer film, and migrate from the metal particle-containing layer to the solid electrolyte layer. Copper ions easily interact with the constituent components (for example, dopants) of the conductive polymer contained in the solid electrolyte layer, thereby migrating the copper ions to the interior of the solid electrolyte layer. The copper ions interact or react with the components (constituent components of the conductive polymer, etc.) present in the surroundings, or are reduced. In addition, the components containing copper reach the dielectric layer. If the solid electrolytic capacitor is exposed to high temperature, the organic components such as the resin binder or its cured product contained in the cathode portion expand, generating stress inside. Therefore, the stress is transmitted to the extremely thin layer, namely the dielectric layer, and is easily damaged. If there is a copper component (for example, copper ions, components that interact with the constituent components of the conductive polymer, metallic copper, copper compounds, etc.) in the damaged portion of the dielectric layer, the anode body and the cathode portion are connected through the copper component, resulting in a relatively large leakage current. If the solid electrolytic capacitor is in a state where moisture in the atmosphere is absorbed during storage, greater stress is applied to the dielectric layer when exposed to high temperatures, which can easily further damage the dielectric layer. Therefore, in this case, the leakage current becomes more significant. It should be noted that in a capacitor that does not have a solid electrolyte layer containing a conductive polymer, there is almost no interaction between copper ions and the constituent components of the conductive polymer, so the migration of copper ions to the dielectric layer side itself is suppressed.
[0024] In view of the above, (1) the solid electrolytic capacitor element of the first aspect of the present disclosure includes: an anode body, a dielectric layer formed on the surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer. The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer, and at least a portion of the cathode portion includes a metal particle-containing layer. The solid electrolyte layer includes a conductive polymer. The metal particles contained in the metal particle-containing layer include first metal particles containing silver. The first metal particles include core particles containing silicon dioxide and a silver-containing covering layer covering the core particles.
[0025] In the solid electrolytic capacitor element disclosed in the present invention, the first metal particles contain core particles containing silicon dioxide, so the silver content in the metal particle-containing layer can be reduced. Therefore, the cost can be suppressed at a low level. In addition, both silver and silicon dioxide are difficult to ionize, and there is almost no interaction with the constituent components of the conductive polymer. Therefore, as in the case of copper particles, the migration of ions of the constituent components of the first metal particles to the solid electrolyte layer is suppressed. Therefore, the leakage current of the solid electrolytic capacitor after being exposed to high temperature can be reduced. Since the occurrence of large leakage current can be suppressed, the short-circuit defect rate can be reduced. In addition, in the present disclosure, even when the solid electrolytic capacitor is exposed to a high humidity environment (including a high temperature and high humidity environment), the leakage current can be suppressed to a small extent. In other words, excellent moisture resistance of the solid electrolytic capacitor can be obtained, and high reliability can be ensured. In the present disclosure, high moisture resistance comparable to that of the existing silver paste layer containing silver particles can also be ensured.
[0026] The covering layer of the first metal particles contains silver, so it is easy to ensure the high conductivity of the metal particle-containing layer. The core particles of the first metal particles are silicon dioxide, so compared with the particles formed entirely of metal, the specific gravity is small. Therefore, in the paste used to form the metal particle-containing layer, the solid electrolyte layer can be covered with a small mass. By using such a paste, the cost per unit volume can be suppressed and a metal particle-containing layer with high conductivity can be formed. Therefore, the initial equivalent series resistance (ESR) of the solid electrolytic capacitor can also be suppressed to a lower level. In addition, the covering layer of the first metal particles contains silver, so compared with the case of copper particles, the oxidation degradation of the first metal particles can be suppressed even when exposed to a high temperature environment or a high temperature and high humidity environment. Therefore, by using the first metal particles, the increase of ESR when exposed to high temperature or when exposed to a high temperature and high humidity environment can be suppressed compared with the case of copper particles. Therefore, the high reliability of the solid electrolytic capacitor can be ensured.
[0027] (2) In the above (1), the ratio of the first metal particles to the total metal particles may be 10% by mass or more. Depending on the ratio of the first metal particles, a cost reduction effect can be obtained. In addition, compared with the case of copper particles, depending on the ratio of the first metal, the effect of suppressing leakage current can be improved.
[0028] (3) In (1) or (2) above, the average aspect ratio of the core particles may be 1 to 10. When the aspect ratio of the core particles is within this range, it is relatively easy to ensure contact between the first metal particles and to highly disperse the first metal particles in the paste.
[0029] (4) In any of (1) to (3) above, the average ratio of the silver-containing coating layer in the first metal particles may be 0.1 mass % or more and 50 mass % or less. When the ratio of the silver-containing coating layer is within such a range, it is easy to achieve a balance between low cost and high conductivity.
[0030] (5) In any of the above (1) to (4), the metal particles may also include second metal particles containing silver. Here, the second metal particles are at least one selected from the group consisting of silver particles and silver alloy particles. The metal particles include second metal particles containing silver, thereby ensuring a higher conductivity of the metal particle-containing layer and suppressing the ESR of the solid electrolytic capacitor to a lower level. In addition, even after exposure to a high temperature environment or a high temperature and high humidity environment, the increase in the ESR of the solid electrolytic capacitor can be suppressed, and high reliability can be ensured.
[0031] (6) The present disclosure also includes a solid electrolytic capacitor comprising: at least one solid electrolytic capacitor element according to any one of (1) to (5) above, and an outer case sealing the solid electrolytic capacitor element.
[0032] (7) In the above (6), the solid electrolytic capacitor may include a plurality of stacked solid electrolytic capacitor elements.
[0033] In this specification, the metal particle-containing layer including the first metal particles may be referred to as a first metal particle-containing layer. In addition, the solid electrolytic capacitor element may be simply referred to as a capacitor element.
[0034] The cathode portion includes, for example, a solid electrolyte layer and a cathode lead layer covering at least a portion of the solid electrolyte layer. In the case where the cathode lead layer and the cathode lead are connected by a conductive adhesive, in this specification, the conductive adhesive layer (hereinafter sometimes referred to as the first conductive adhesive layer) sandwiched between the cathode lead layer and the cathode lead is also included in the cathode portion. In the case where a plurality of capacitor elements are fixed by a conductive adhesive in a solid electrolytic capacitor including a plurality of capacitor elements, in this specification, the conductive adhesive layer (hereinafter sometimes referred to as the second conductive adhesive layer) used to fix adjacent capacitor elements is also included in the cathode portion (more specifically, the cathode portion of the capacitor element on either side).
[0035] In any of the above (1) to (7), the cathode portion may also include a layer containing first metal particles in at least a portion of at least one of the group consisting of a cathode lead layer, a first conductive adhesive layer, and a second conductive adhesive layer. For example, the cathode lead layer may include: a first layer (also referred to as a carbon layer) containing conductive carbon and covering at least a portion of the solid electrolyte layer, and a layer containing first metal particles as a second layer covering at least a portion of the first layer. The cathode portion may also include a metal particle-containing layer other than the layer containing first metal particles (hereinafter sometimes referred to as a layer containing second metal particles or a layer containing third metal particles). For example, the cathode lead layer includes a carbon layer as a first layer and a layer containing second metal particles as a second layer, and may also include a layer containing first metal particles as a first conductive adhesive layer sandwiched between the layer containing second metal particles and the cathode lead. In addition, the solid electrolytic capacitor may include a laminated body in which a plurality of capacitor elements including a cathode lead layer including a first layer and a layer containing second metal particles as a second layer are laminated via a layer containing first metal particles as a second conductive adhesive layer. In such a laminated body, the cathode lead layer and the cathode lead of each capacitor element may be connected via a layer containing third metal particles or a layer containing first metal particles as a first conductive adhesive layer.
[0036] The following describes the capacitor element and solid electrolytic capacitor of the present invention in more detail, including the above (1) to (7). As long as at least one of the constituent elements described below can be combined technically, at least one of the above (1) to (5) of the solid electrolytic capacitor element of the present invention and (6) to (7) of the solid electrolytic capacitor can be arbitrarily combined.
[0037] [Solid electrolytic capacitors]
[0038] A solid electrolytic capacitor includes one or two or more capacitor elements.
[0039] (Capacitor Components)
[0040] (Anode)
[0041] The anode body included in the capacitor element may include a valve metal, an alloy including a valve metal, a compound including a valve metal, etc. The anode body may include one of these materials, or a combination of two or more. Examples of valve metals include aluminum, tantalum, niobium, and titanium.
[0042] The anode body has a porous portion at least on the surface. With such a porous portion, the anode body has a fine concavo-convex shape at least on the surface. The anode body having a porous portion on the surface is obtained, for example, by roughening the surface of a substrate (a sheet-like (for example, foil-like, plate-like) substrate, etc.) containing a valve-acting metal. Roughening can be performed, for example, by etching treatment, etc. In addition, the anode body can also be a molded body containing particles of a valve-acting metal or a sintered body thereof. The molded body and the sintered body can each constitute a porous portion as a whole. The molded body and the sintered body can each be in the shape of a sheet, or in the shape of a cuboid, a cube, or shapes similar to these.
[0043] The anode body generally has an anode lead-out portion and a cathode forming portion. The porous portion may be formed in the cathode forming portion, or may be formed in the cathode forming portion and the anode lead-out portion. The cathode portion is generally formed in the cathode forming portion of the anode body through a dielectric layer. The anode lead-out portion is used, for example, to electrically connect to an external electrode on the anode side.
[0044] (Dielectric layer)
[0045] The dielectric layer is formed, for example, in a manner covering at least a portion of the surface of the anode body. The dielectric layer is an insulating layer that functions as a dielectric. The dielectric layer is formed by anodic oxidation of the valve metal on the surface of the anode body by chemical conversion treatment or the like. The dielectric layer is formed on the porous surface of the anode body, so the surface of the dielectric layer has a fine concavo-convex shape as described above.
[0046] The dielectric layer includes an oxide of a valve metal. For example, when tantalum is used as the valve metal, the dielectric layer includes Ta2O5, and when aluminum is used as the valve metal, the dielectric layer includes Al2O3. It should be noted that the dielectric layer is not limited to these examples, as long as it functions as a dielectric.
[0047] (Cathode)
[0048] The cathode portion is formed so as to cover at least a portion of the dielectric layer formed on the surface of the anode body. Each layer constituting the cathode portion can be formed by a known method according to the layer structure of the cathode portion.
[0049] The cathode portion includes, for example, a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer. The cathode portion may further include a first conductive adhesive layer sandwiched between the cathode lead layer and the cathode lead. In addition, the cathode portion may include a second conductive adhesive layer for fixing adjacent capacitor elements.
[0050] As described above, the layer containing the first metal particles may be included in at least a portion of at least one of the group consisting of a cathode lead layer, a first conductive adhesive layer, and a second conductive adhesive layer. Regarding the effect on the leakage current, if the first conductive adhesive layer is larger than the second conductive adhesive layer, the cathode lead layer closer to the solid electrolyte layer is larger. In the present disclosure, the cathode portion can more significantly reduce the leakage current of the solid electrolytic capacitor after being exposed to high temperature when at least the cathode lead layer includes a layer containing the first metal particles.
[0051] Hereinafter, components of the cathode portion will be described.
[0052] (Solid electrolyte layer)
[0053] The solid electrolyte layer is formed on the surface of the anode body through the dielectric layer in a manner covering the dielectric layer. The solid electrolyte layer does not necessarily have to cover the entire dielectric layer (the entire surface), and can be formed in a manner covering at least a portion of the dielectric layer. The solid electrolyte layer constitutes at least a portion of the cathode portion in the solid electrolytic capacitor.
[0054] The solid electrolyte layer contains a conductive polymer. The conductive polymer includes, for example, a conjugated polymer and a dopant. The solid electrolyte layer may further contain an additive as required.
[0055] As conjugated polymers, known conjugated polymers used in solid electrolytic capacitors, such as π-conjugated polymers, can be listed. As conjugated polymers, for example, polymers with polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene, polyphenylene vinylene, polyphenylene, and polythiophene vinylene as basic skeletons can be listed. Among these, polymers with polypyrrole, polythiophene, or polyaniline as basic skeletons are preferred. The above-mentioned polymers include at least one monomer unit constituting the basic skeleton. The monomer unit also includes a monomer unit having a substituent. The above-mentioned polymers also include homopolymers and copolymers of two or more monomers. For example, polythiophene includes poly (3,4-ethylenedioxythiophene) (PEDOT) and the like.
[0056] The solid electrolyte layer may contain one type of conjugated polymer or a combination of two or more types.
[0057] The weight average molecular weight (Mw) of the conjugated polymer is not particularly limited, and is, for example, 1,000 or more and 1,000,000 or less.
[0058] It should be noted that in this specification, the weight average molecular weight (Mw) is a value measured by gel permeation chromatography (GPC) in terms of polystyrene. It should be noted that GPC is usually measured using a polystyrene silica gel column and water / methanol (volume ratio 8 / 2) as a mobile phase.
[0059] As the dopant, for example, at least one selected from the group consisting of anions and polyanions can be cited.
[0060] Examples of anions include sulfate ions, nitrate ions, phosphate ions, borate ions, organic sulfonate ions, and carboxylate ions, but are not particularly limited. Examples of dopants that generate sulfonate ions include benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid.
[0061] Examples of the polyanion include polymer anions, etc. The solid electrolyte layer may contain, for example, a conjugated polymer containing a monomer unit corresponding to a thiophene compound, and a polymer anion.
[0062] As the polymer anion, for example, a polymer having a plurality of anionic groups can be cited. As such a polymer, a polymer containing a monomer unit having an anionic group can be cited. As the anionic group, a sulfonic acid group, a carboxyl group, etc. can be cited.
[0063] In the solid electrolyte layer, the anionic group of the dopant may be included in a free form, anionic form or salt form, or in a form of binding or interacting with a conjugated polymer. In this specification, all of these forms are included, and sometimes referred to as "anionic group", "sulfonic acid group" or "carboxyl group" or the like.
[0064] Examples of the polymer anion having a carboxyl group include polyacrylic acid, polymethacrylic acid, and a copolymer using at least one of acrylic acid and methacrylic acid, but the present invention is not limited to these.
[0065] As the polymer anion having a sulfonic acid group, for example, a high molecular weight polysulfonic acid can be cited. Specific examples of high molecular weight polysulfonic acids include polyethylene sulfonic acid, polystyrene sulfonic acid (including copolymers and substituted products with substituents, etc.), polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacryloyl sulfonic acid, poly (2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyester sulfonic acid (aromatic polyester sulfonic acid, etc.), and phenol sulfonic acid novolac resin, but are not limited to these.
[0066] The amount of the dopant contained in the solid electrolyte layer is, for example, 10 to 1000 parts by mass, or 20 to 500 parts by mass or 50 to 200 parts by mass, based on 100 parts by mass of the conjugated polymer.
[0067] The solid electrolyte layer may further include at least one selected from the group consisting of known additives and known conductive materials other than conductive polymers as needed. As the conductive material, for example, at least one selected from the group consisting of conductive inorganic materials such as manganese dioxide and TCNQ complex salts can be cited.
[0068] In addition, a layer for improving adhesion may be interposed between the dielectric layer and the solid electrolyte layer.
[0069] The solid electrolyte layer may be a single layer or may be composed of multiple layers. For example, the solid electrolyte layer may be composed of a first solid electrolyte layer covering at least a portion of the dielectric layer and a second solid electrolyte layer covering at least a portion of the first solid electrolyte layer. The type, composition, content, etc. of the conjugated polymer, dopant, additive, etc. contained in each layer may be different or the same in each layer.
[0070] The solid electrolyte layer is formed, for example, by polymerizing the precursor on the dielectric layer using a treatment solution containing a precursor of a conjugated polymer and a dopant. The polymerization can be carried out by at least one of chemical polymerization and electrolytic polymerization. As a precursor of a conjugated polymer, monomers, oligomers or prepolymers can be listed. The solid electrolyte layer can also be formed by attaching a treatment solution (for example, a dispersion or solution) containing a conductive polymer to the dielectric layer and then drying it. As a dispersion medium (or solvent), for example, at least one selected from the group consisting of water and an organic solvent can be listed. The treatment solution may further contain other components (selected from at least one of the group consisting of a dopant, and an additive, etc.). The solid electrolyte layer can also be formed, for example, using a treatment solution containing a conductive polymer (for example, PEDOT), a dopant (for example, a polyanion such as polystyrene sulfonic acid), and additives as needed.
[0071] When a treatment liquid containing a conjugated polymer precursor is used, an oxidant is used to polymerize the precursor. The oxidant may be contained in the treatment liquid as an additive. In addition, the oxidant may be applied to the anode body before or after the treatment liquid is brought into contact with the anode body on which the dielectric layer is formed. Examples of such an oxidant include an oxidant that can generate Fe 3+ Compounds (ferric sulfate, etc.), persulfates (sodium persulfate, ammonium persulfate, etc.), hydrogen peroxide. The oxidizing agent may be used alone or in combination of two or more.
[0072] The process of forming a solid electrolyte layer by immersion in a treatment solution and polymerization (or drying) may be performed once or repeatedly. In each case, the composition and viscosity of the treatment solution may be the same, or at least one of the conditions may be changed.
[0073] (Cathode extraction layer)
[0074] The cathode lead layer may include at least a first layer that is in contact with the solid electrolyte layer and covers at least a portion of the solid electrolyte layer, and may include the first layer and a second layer that covers at least a portion of the first layer.
[0075] As the first layer, for example, a layer containing conductive particles, a metal foil, etc. can be cited. As the conductive particles, for example, at least one selected from conductive carbon and metal powder can be cited. For example, the cathode lead layer can also be composed of a layer containing conductive carbon (carbon layer) as the first layer and a layer containing metal powder or a metal foil as the second layer. When a metal foil is used as the first layer, the cathode lead layer can also be composed of the metal foil.
[0076] Examples of the conductive carbon include graphite (artificial graphite, natural graphite, etc.).
[0077] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. As such a second layer, for example, a metal particle-containing layer formed using a paste containing metal powder and a resin binder can be cited. As the resin binder, a thermoplastic resin can also be used, but a thermosetting resin such as an imide resin and an epoxy resin is preferably used. From the viewpoint of easily obtaining high conductivity of the second layer, silver-containing particles can also be used as metal powder. As silver-containing particles, first metal particles, second metal particles (specifically, silver particles, and silver alloy particles) and the like can be cited. The second layer can contain one type of silver-containing particles, or a combination of two or more types. From the viewpoint of ensuring higher conductivity of the second layer, silver particles and first metal particles are preferred as silver-containing particles. Silver particles may contain a small amount of impurities. The second layer containing silver-containing particles may be a layer containing first metal particles or a layer containing second metal particles. The second layer may, for example, contain silver particles and silver alloy particles, may contain first metal particles, or may contain first metal particles and at least one of silver particles and silver alloy particles.
[0078] When a metal foil is used as the first layer, the type of metal is not particularly limited. The metal foil preferably uses a valve metal (aluminum, tantalum, niobium, etc.) or an alloy containing a valve metal. The surface of the metal foil may be roughened as needed. A chemical conversion coating may be provided on the surface of the metal foil, or a coating of a metal (different metal) or a non-metal different from the metal constituting the metal foil may be provided. As different metals or non-metals, for example, metals such as titanium or non-metals such as carbon (conductive carbon, etc.) may be listed.
[0079] The above-mentioned coating of different kinds of metals or non-metals (for example, conductive carbon) may be used as the first layer, and the above-mentioned metal foil may be used as the second layer.
[0080] When the cathode lead layer includes a layer containing first metal particles, the cathode lead layer may be composed of the layer containing first metal particles as a whole, the first layer may be composed of the layer containing first metal particles, or the second layer may be composed of the layer containing first metal particles. For example, the cathode lead layer may include: a first layer (carbon layer) containing conductive carbon, and a second layer containing a layer containing first metal particles covering at least a portion of the first layer.
[0081] The cathode lead layer can be formed by a known method according to its layer structure. For example, in the case where the cathode lead layer includes a metal foil as the first layer or the second layer, the first layer or the second layer can be formed by stacking the metal foil in a manner that covers at least a portion of the solid electrolyte layer or the first layer. The first layer containing conductive particles is formed, for example, by applying a conductive paste or liquid dispersion containing conductive particles and a resin binder (water-soluble resin, curable resin, etc.) as required to the surface of the solid electrolyte layer. The second layer containing metal powder is formed, for example, by applying a paste containing metal powder and a resin binder to the surface of the first layer. In the formation process of the cathode lead layer, drying treatment, heat treatment, etc. can be performed as needed.
[0082] From the viewpoint of suppressing the increase of leakage current accompanying the migration of copper ions in a high temperature environment, the cathode lead layer (metal particle-containing layer, etc.) preferably does not contain copper particles and copper alloy particles. From the same viewpoint, even if the cathode lead layer contains at least one of copper particles and copper alloy particles, the total ratio of these particles is preferably small. For example, the total ratio of copper particles and copper alloy particles to the total metal particles contained in the metal particle-containing layer is, for example, less than 10% by mass, more preferably less than 5% by mass or less than 1% by mass. In the case where the cathode lead layer contains a metal foil, the metal foil does not contain copper, or in the case where the metal foil contains copper, the content of copper in the metal foil is also preferably small. The content of copper in the metal foil is, for example, less than 10% by mass, more preferably less than 5% by mass or less than 1% by mass. In addition, the metal-containing layer (first layer and second layer, etc.) constituting the cathode lead layer does not contain copper, or even if it contains copper, the ratio of copper to the total metal contained in the metal-containing layer is less than 10% by mass, and can also be less than 5% by mass or less than 1% by mass.
[0083] (First Conductive Adhesive Layer)
[0084] The solid electrolytic capacitor may include a cathode lead. In the solid electrolytic capacitor, the cathode lead is connected to the cathode lead layer by means of a first conductive adhesive layer. In the case where the solid electrolytic capacitor includes a plurality of capacitor elements, the cathode lead layer of a portion of the capacitor elements is connected to the cathode lead by means of the first conductive adhesive layer. The cathode lead layer of the capacitor element is electrically connected to the cathode lead by means of the first conductive adhesive layer.
[0085] The first conductive adhesive layer can be formed using a known conductive adhesive. As a known conductive adhesive, for example, a paste containing conductive particles and a resin binder (curable resin, etc.) can be cited. The first conductive adhesive layer formed using a known conductive adhesive can be a layer containing second metal particles formed using a known silver-containing adhesive (for example, a silver-containing paste). Such a first conductive adhesive layer can be formed, for example, by configuring the above-mentioned paste (including a silver-containing paste) in a manner clamped between the cathode lead layer and the cathode lead. For example, the above-mentioned paste is applied or transferred to a portion of the surface of the cathode lead layer, and a portion of the end side of the cathode lead can be overlapped on the coating film of the formed paste. In the formation process of the first conductive adhesive layer, drying treatment, heating treatment, etc. can be performed as needed.
[0086] The first conductive adhesive layer may be a layer containing first metal particles. In this case, the cathode portion includes the layer containing first metal particles interposed between the cathode lead layer and the cathode lead.
[0087] (Second Conductive Adhesive Layer)
[0088] In the case where the solid electrolytic capacitor includes a plurality of capacitor elements, the plurality of capacitor elements may be fixed by means of the second conductive adhesive layer. For example, in the case where the solid electrolytic capacitor includes a stack of a plurality of capacitor elements, the plurality of capacitor elements may also be stacked across the second conductive adhesive layer. The second conductive adhesive layer may also be in contact with the cathode lead layer of each capacitor element. The plurality of capacitor elements are electrically connected through the second conductive adhesive layer.
[0089] The second conductive adhesive layer can be formed using a known conductive adhesive. As a known conductive adhesive, for example, a paste containing conductive particles and a resin binder (curable resin, etc.) can be cited. The second conductive adhesive layer formed using a known conductive adhesive can be a layer containing third metal particles formed using a known silver-containing adhesive (for example, a silver-containing paste). Such a second conductive adhesive layer is formed, for example, by configuring the above-mentioned paste (including a silver-containing paste) in a manner clamped between adjacent capacitor elements. For example, the above-mentioned paste is applied or transferred to a portion of the surface of the cathode lead layer of the capacitor element, and other capacitor elements can be overlapped on the coating film of the formed paste. In the formation process of the second conductive adhesive layer, drying treatment, heat treatment, etc. can be performed as needed.
[0090] The second conductive adhesive layer may be a layer containing the first metal particles. In this case, adjacent solid electrolytic capacitor elements are fixed via the layer containing the first metal particles.
[0091] The first metal particle-containing layer included in the cathode portion will be described in detail below.
[0092] (Layer containing first metal particles)
[0093] The first metal particle-containing layer contains metal particles. The first metal particle-containing layer generally contains a resin binder or a cured product thereof.
[0094] The metal particles include first metal particles. The metal particles may further include second metal particles, and the second metal particles are specifically at least one selected from the group consisting of silver particles and silver alloy particles. In addition to the first metal particles, or the first metal particles and the second metal particles, the metal particles may further include third metal particles other than the first metal particles and the second metal particles.
[0095] (First Metal Particle)
[0096] The first metal particle includes a core particle and a silver-containing covering layer covering the core particle. The core particle includes, for example, silicon dioxide. The silicon dioxide may be crystalline or amorphous. In addition, the silicon dioxide may be porous or non-porous. The core particle may be fused silica.
[0097] The average aspect ratio of the core particles is, for example, 1 to 100, and may be 1 to 20. From the viewpoint of easily forming a relatively uniform silver-containing covering layer, the average aspect ratio is preferably 1 to 10, and more preferably 1 to 5. In addition, when the average aspect ratio is within such a range, it is easy to disperse in the paste for forming the first metal particle-containing layer, and the first metal particles are easily arranged in the first metal particle-containing layer with high filling properties.
[0098] The shape of the core particles is not particularly limited, and may be spherical (including ellipsoidal, etc.), flake, irregular, etc. From the viewpoint of being easy to form a relatively uniform silver-containing coating layer, being easy to disperse in the paste, and being easy to highly fill in the layer containing the first metal particles, the shape of the core particles is preferably spherical (including ellipsoidal, etc.).
[0099] In the present specification, spherical particles refer to particles having a sphericity of 0.6 or more and 1 or less. Flaky particles refer to particles having a flat shape or a flaky shape.
[0100] The silver-containing covering layer may be composed of silver or a silver alloy. From the viewpoint of obtaining high conductivity, the silver-containing covering layer is preferably composed of silver. In this case, the silver may contain a small amount of impurities.
[0101] The average ratio of the silver-containing coating layer in the first metal particles can be, for example, 0.1% by mass or more and 50% by mass or less, 1% by mass or more and 40% by mass or less, 5% by mass or more and 30% by mass or less, or 10% by mass or more and 30% by mass or less. When the ratio of the silver-containing coating layer is within such a range, most of the surface of the core particle is covered with the silver-containing coating layer, and it is easy to ensure the high conductivity of the first metal particles. In addition, it is easy to adjust the specific gravity of the first metal particles to an appropriate range, and it is easy to highly disperse the first metal particles in the paste. Therefore, it is easy to balance the cost reduction effect and the high conductivity of the layer containing the first metal particles.
[0102] The first metal particles may include one type of particles, or may include a combination of two or more types of particles having different compositions of at least one of the core particles and the silver-containing coating layer.
[0103] The shape of the first metal particles is not particularly limited, and may be spherical (including ellipsoidal, etc.), flake, irregular, etc. The first metal particles may include particles of one shape, or may be a combination of particles of two or more shapes. The first metal particles preferably include at least spherical particles. In this case, it is easy to disperse in the paste, and it is easy to arrange the first metal particles in the layer containing the first metal particles with high filling properties. In addition, in the layer containing the first metal particles, a large number of contact points between the particles can be ensured. Therefore, a higher conductivity of the layer containing the first metal particles can be ensured. As a result, the effect of suppressing the initial ESR to a lower level tends to be improved. The first metal particles may, for example, include spherical particles and particles of other shapes.
[0104] In this specification, the sphericity of a particle can be estimated by obtaining a cross-sectional image containing a plurality of particles (for example, more than 10 particles) and analyzing the contour lines of the particles contained in the image. The ratio of the diameter of a circle (hereinafter referred to as an "equivalent circle") having an area equal to that within the closed curve formed by the contour line to the diameter of the smallest circle circumscribed with the contour line is calculated. The average value of the plurality of particles relative to the ratio is taken as the sphericity of the particle. For example, in the case of particles containing spherical particles and shapes other than spherical particles, a plurality of particles are selected from the spherical particles, and the sphericity is calculated using the above steps. The cross-sectional image may be an image obtained using a scanning electron microscope (SEM).
[0105] The above-mentioned cross-sectional image can be obtained, for example, using the following steps. First, a solid electrolytic capacitor is embedded in a curable resin to cure the curable resin. The cured product is wet-ground or dry-ground to expose a cross section parallel to the thickness direction of the cathode portion (a cross section that can confirm the stacking state of each layer of the cathode portion). By smoothing the exposed cross section with ion milling, a sample for photographing can be obtained. As needed, the cross-sectional image can be analyzed using an image analysis-type particle size distribution measurement software (e.g., MAC-View (MOUNTECH Co., Ltd.)), and the outline of each particle can also be determined.
[0106] The average aspect ratio of the core particles can be obtained from the cross-sectional image described above. To be more specific, in the cross-sectional image, a plurality of (for example, more than 10) first metal particles in which the core particles can be observed are arbitrarily selected to obtain the maximum length a of each core particle. For each core particle, the maximum length b in a direction orthogonal to the maximum length a is obtained, and the ratio a / b is used as the aspect ratio of each core particle. For multiple core particles, the ratio a / b is averaged to obtain the average aspect ratio of the core particles.
[0107] The average particle size of the first metal particles may be, for example, 1 μm to 20 μm, or 1 μm to 10 μm. When the average particle size is within this range, it is easy to ensure contact between the first metal particles and to obtain higher conductivity of the layer containing the first metal particles.
[0108] In this specification, the average particle size of the particles is estimated by obtaining a cross-sectional image containing a plurality of particles (for example, more than 10) and analyzing the contour lines of the particles contained in the image. The diameter of an equivalent circle equal to the area within the closed curve formed by the contour line is obtained and averaged to obtain the average particle size. The preparation of the sample for the cross-sectional image and the analysis of the image are performed, for example, in the same steps as those for obtaining the sphericity. As needed, the cross-sectional image is analyzed using the above-mentioned software to determine the contour of each particle, and the diameter of the equivalent circle or the smallest circumscribed circle with the same area as the area surrounded by the contour can also be obtained.
[0109] The ratio of the first metal particles contained in the layer containing the first metal particles to the entire metal particles is, for example, 10% by mass or more, 30% by mass or more, 50% by mass or more, or 60% by mass or more. When the ratio of the first metal particles increases, the average specific gravity of the metal particles decreases, thereby having the effect of reducing the cost per unit volume. From this point of view, the ratio of the first metal particles contained in the layer containing the first metal particles to the entire metal particles can be 80% by mass or more, and can be greater than 90% by mass. The ratio of the first metal particles contained in the layer containing the first metal particles to the entire metal particles is 100% by mass or less.
[0110] The first metal particles can be obtained by a known method or a method based thereon. In addition, commercially available products can also be used as the first metal particles. The covering of the core particles with the silver-containing covering layer can also be performed by a plating method, a vapor phase method (evaporation, sputtering, etc.), etc.
[0111] In the layer containing the first metal particles, the mass ratio of Si to the metal such as Ag (=Si / metal (Ag, etc.)) is 0.1 to 10, 0.2 to 5.0, or 0.2 to 3.0. It should be noted that the mass ratio of Si to the metal is obtained by using an electron probe micro analyzer (EPMA: Electron Probe Micro Analyzer) on the cross section of the layer containing the first metal particles.
[0112] In the cross section of the layer containing the first metal particles, the ratio of the area occupied by the first metal particles to the area occupied by the metal particles as a whole (= the area of the first metal particles / the area of the metal particles as a whole) may be 0.20 or more and 1.00 or less (e.g., 0.50 or more and 1.00 or less), or 0.40 or more and 1.00 or less (e.g., 0.40 or more and 0.95 or less). It should be noted that the area ratio is obtained by using the above-mentioned cross-sectional image and energy dispersive X-ray spectroscopy (EDX).
[0113] (Second Metal Particles)
[0114] Among the above-mentioned second metal particles, silver particles are preferred. The silver particles may contain a small amount of impurities. The second metal particles may include silver particles and silver alloy particles. The content of silver particles in the second metal particles is, for example, 80% by mass or more, and may be 90% by mass or more. The content of silver particles in the second metal particles is 100% by mass or less. The second metal particles may also be composed of only silver particles.
[0115] The shape of the second metal particles is not particularly limited, and may be spherical (including ellipsoidal, etc.), flaky, irregular, etc. The second metal particles may include particles of one shape, or may be a combination of particles of two or more shapes. For example, the second metal particles may include at least one selected from the group consisting of spherical particles and flaky particles. The second metal particles preferably include at least spherical particles. In this case, it is easy to disperse in the paste, and it is easy to make the second metal particles highly filled in the layer containing the second metal particles. In addition, in the layer containing the second metal particles, a large number of contacts between the particles can be ensured. Therefore, a higher conductivity of the layer containing the second metal particles can be ensured. As a result, there is a tendency to increase the effect of suppressing the initial ESR to a lower level. The second metal particles may, for example, include spherical particles and particles of other shapes.
[0116] The average particle diameter of the second metal particles is, for example, 0.01 μm or more and 50 μm or less, and may be 0.1 μm or more and 20 μm or less.
[0117] The aspect ratio and sphericity of the second metal particles can be selected from the ranges described for the first metal particles. The aspect ratio, sphericity and average particle size of the second metal particles are determined based on the first metal particles.
[0118] (Third Metal Particles)
[0119] As the third metal particles other than the first metal particles and the second metal particles, for example, metal particles substantially not containing precious metals such as silver or gold can be cited. As such third metal particles, for example, copper particles, copper alloy particles, nickel particles, and nickel alloy particles can be cited. It should be noted that metal particles containing precious metals as impurities (excluding the first metal particles and the second metal particles) are included in the third metal particles.
[0120] The case where the layer containing the first metal particles contains the third metal particles is advantageous in terms of reducing costs. However, as mentioned above, the total ratio of copper particles and copper alloy particles is preferably low, and it is also preferred that copper particles and copper alloy particles are not included. In addition, from the viewpoint of easily ensuring higher conductivity, the content of the third metal particles in the entire metal particles contained in the layer containing the first metal particles is preferably low. In the entire metal particles, the total content of the first metal particles and the second metal particles is, for example, 90% by mass or more, and can be 95% by mass or more. In the entire metal particles, the total content of the first metal particles and the second metal particles is less than 100% by mass. The metal particles can be composed only of the first metal particles, or the metal particles can be composed only of the first metal particles and the second metal particles.
[0121] (resin binder)
[0122] Examples of the resin binder include thermoplastic resin materials, curable resin materials, etc. The first metal particle-containing layer preferably includes a cured product of the resin binder (specifically, a cured product of a curable resin material) from the viewpoint of relatively small deformation when exposed to high temperatures.
[0123] The first metal particle-containing layer is formed using, for example, a conductive paste containing metal particles and a resin binder. For example, the first metal particle-containing layer is formed by heating a coating of the conductive paste to cure the resin binder.
[0124] As a curable resin material, there can be listed a resin composition comprising a curable resin (for example, a thermosetting resin), a component related to the curing of the curable resin, and at least one selected from the group consisting of an additive and a liquid medium as required. As a component related to the curing of the curable resin, according to the type of the curable resin, for example, a polymerization initiator, a curing agent, a curing accelerator, a cross-linking agent, and a curing catalyst can be listed. Such components can be used alone or in combination of two or more. As additives, for example, known additives used in conductive pastes for solid electrolytic capacitors can be listed.
[0125] Preferred curable resins include epoxy resins, polyamide-imide resins, polyimide resins, phenolic resins, etc. The resin binder may contain one type of curable resin or a combination of two or more types.
[0126] In the layer containing the first metal particles, the amount of the resin binder or its cured product can be, for example, 2 parts by mass or more and 25 parts by mass or less, 5 parts by mass or more and 20 parts by mass or less, or 10 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the metal particles. However, the amount is not limited to these ranges.
[0127] (other)
[0128] The content of the metal particles in the layer containing the first metal particles is determined, for example, by taking into account the balance between conductivity and adhesion. The content of the metal particles can be, for example, greater than 80% by mass and less than 98% by mass, or greater than 85% by mass and less than 96% by mass. However, the ratio of the metal particles is not limited to these ranges. It should be noted that the content of the metal particles in the layer containing the first metal particles is equivalent to the ratio (mass %) of the metal particles in the total dry solid content (the total amount of components other than the liquid medium (i.e., solvent)) contained in the paste used to form the layer containing the first metal particles. The liquid medium does not contain raw materials (monomers, etc.) of the solidified material of the resin binder.
[0129] The thickness of the layer containing the first metal particles is, for example, 0.5 μm or more and 100 μm or less, may be 1 μm or more and 50 μm or less, or may be 1 μm or more and 20 μm or less.
[0130] The thickness of the first metal particle-containing layer is determined by measuring the thickness of the first metal particle-containing layer at a plurality of locations (eg, 10 locations) in a cross-sectional image obtained by SEM and averaging the measured thicknesses.
[0131] The thickness of the first metal particle-containing layer is measured using, for example, a cross-sectional image of a portion of the capacitor element including the first metal particle-containing layer using an SEM. The cross-sectional image is prepared, for example, by the same procedure as that for determining the sphericity.
[0132] The layer containing the first metal particles can be formed by applying a conductive paste containing at least the first metal particles, the second metal particles, and a resin binder so as to cover at least a portion of at least one member (also referred to as a constituent member) constituting the capacitor element (more specifically, the cathode portion), and performing a heat treatment. As constituent members to which the conductive paste is applied, there can be cited layers in the cathode portion that are in contact with the layer containing the first metal particles, such as a solid electrolyte layer, a cathode lead layer, a first layer or a second layer constituting the cathode lead layer, and a cathode lead.
[0133] The conductive paste can be obtained by mixing the constituent components. The mixing can be performed by a known method. The liquid medium used in the preparation of the conductive paste can be any medium that is liquid at the temperature at which the conductive paste is prepared or imparted, and can be a medium that is liquid at room temperature (for example, 20°C to 35°C). As the liquid medium, for example, an organic solvent is used. As the liquid medium, an organic solvent and water can also be used in combination. The liquid medium can be selected based on the curable resin, the components related to curing, and the types of additives.
[0134] (other)
[0135] The solid electrolytic capacitor may be a winding type, a chip type, or a stacked type. In the case where the solid electrolytic capacitor includes a plurality of capacitor elements, each capacitor element may be, for example, a winding type or a stacked type. For example, a stacked solid electrolytic capacitor includes a plurality of stacked capacitor elements. The configuration of the capacitor element may be selected according to the type of the solid electrolytic capacitor.
[0136] In the capacitor element, for example, one end of the cathode lead is electrically connected to the cathode lead-out layer. For example, one end of the anode lead is electrically connected to the anode body (specifically, the anode lead-out portion). The other end of the anode lead and the other end of the cathode lead are respectively led out from the outer shell. The other end of each lead exposed from the outer shell is used to be soldered to the substrate on which the solid electrolytic capacitor is to be mounted, and is electrically connected to the external electrode. At least a portion of the external electrode constitutes the external terminal of the solid electrolytic capacitor. As each lead, a lead wire can be used, or a lead frame can be used. In addition, not limited to the case of using a lead wire, the end face of the anode lead-out portion can also be exposed from the outer shell and connected to the external electrode. The cathode foil can also be connected to the cathode lead-out layer, and the end face of the cathode foil can be exposed from the outer shell and connected to the external electrode. The end face of the other end of the lead connected to the cathode lead-out layer can also be exposed from the outer shell and connected to the external electrode.
[0137] The capacitor element is sealed, for example, by an outer shell. For example, the material resin of the capacitor element and the outer shell (for example, uncured thermosetting resin and filler) is housed in a mold, and the capacitor element can also be sealed with a resin outer shell by using transfer molding, compression molding, etc. At this time, the part on the other end side of the anode lead and the part on the other end side of the cathode lead derived from the capacitor element are exposed from the mold respectively. In addition, the capacitor element can also be housed in a bottomed outer shell in a manner such that the part on the other end side of the anode lead and the part on the other end side of the cathode lead are located on the opening side of the bottomed outer shell, and the opening of the bottomed outer shell is sealed with a sealant to form a solid electrolytic capacitor.
[0138] Figure 1 2 is a cross-sectional view schematically showing the structure of a solid electrolytic capacitor according to an embodiment of the present disclosure. Figure 1 As shown, the solid electrolytic capacitor 1 includes: a capacitor element 2, a resin case 3 that seals the capacitor element 2, and an anode terminal 4 and a cathode terminal 5, each of which at least a portion is exposed outside the resin case 3. The anode terminal 4 and the cathode terminal 5 can be made of metal such as copper or a copper alloy. The resin case 3 has a substantially rectangular parallelepiped shape, and the solid electrolytic capacitor 1 also has a substantially rectangular parallelepiped shape.
[0139] The capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. The cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7, and a cathode lead layer 10 covering the solid electrolyte layer 9. The cathode lead layer 10 includes a first layer 11 covering the solid electrolyte layer 9, and a second layer 12 covering the first layer.
[0140] Anode body 6 includes a region facing cathode portion 8 and a region not facing cathode portion 8. In the region not facing cathode portion 8 of anode body 6, a portion adjacent to cathode portion 8 is formed with an insulating separation portion 13 in a band-like manner covering the surface of anode body 6, and contact between cathode portion 8 and anode body 6 is limited. The other portion of the region not facing cathode portion 8 of anode body 6 is electrically connected to anode terminal 4 by welding. Cathode terminal 5 is electrically connected to cathode portion 8 via first conductive adhesive layer 14.
[0141] In the example shown in the figure, at least one of the second layer 12 and the first conductive adhesive layer 14 (preferably at least the second layer 12) can be a layer containing first metal particles. In this way, by including the layer containing the first metal particles in the cathode portion, the cost can be reduced and the leakage current of the solid electrolytic capacitor after being exposed to high temperature can be suppressed to a low level. In addition, the first metal particles can ensure high conductivity of the layer containing the first metal particles, so that the initial ESR can be suppressed to a low level.
[0142] Hereinafter, the present invention will be specifically described based on Examples and Reference Examples, but the present invention is not limited to the following Examples.
[0143] 《Examples 1 to 3 and Comparative Example 1》
[0144] Capacitor elements or solid electrolytic capacitors were produced and evaluated according to the following procedures.
[0145] (1) Preparation of anode body
[0146] The anode body was produced by roughening both surfaces of an aluminum foil (thickness: 100 μm) as a substrate by etching.
[0147] (2) Formation of dielectric layer
[0148] The other end portion of the anode body was immersed in a chemical conversion solution, and a direct current voltage of 2.5 V was applied for 20 minutes to form a dielectric layer containing aluminum oxide.
[0149] (3) Formation of solid electrolyte layer
[0150] An aqueous solution containing a pyrrole monomer and p-toluenesulfonic acid was prepared. The concentration of the monomer in the aqueous solution was 0.5 mol / L, and the concentration of p-toluenesulfonic acid was 0.3 mol / L.
[0151] The anode body and the counter electrode having the dielectric layer formed in (2) above were immersed in the obtained aqueous solution and electrolytic polymerization was performed at 25° C. at a polymerization voltage of 3 V (polymerization potential relative to a silver reference electrode) to form a solid electrolyte layer.
[0152] (4) Formation of cathode part
[0153] The anode body obtained in (3) above is immersed in a dispersion of graphite particles dispersed in water, taken out of the dispersion and then dried to form a first layer (carbon layer) at least on the surface of the solid electrolyte layer. Drying is performed at 150° C. for 30 minutes.
[0154] Next, a conductive paste containing metal particles shown in the table was applied to the surface of the first layer, and a heat treatment was performed at 210°C for 10 minutes to form a second layer as a metal particle-containing layer. In this way, a cathode extraction layer consisting of the first layer and the second layer was formed. The thickness of the second layer was about 10 μm. In this way, a capacitor element was produced.
[0155] The conductive paste used in the formation of the second layer is prepared by mixing the metal particles, resin binder, and liquid medium (or dispersion or solution containing resin binder) shown in the table. An epoxy resin composition is used as a resin binder. The ratio of metal particles to the total amount of components other than the liquid medium in the conductive paste (the total dry solid content) is 87.5% by mass. The ratio of the resin binder to the total amount of 100 parts by mass of the metal particles is 14 parts by mass. As each metal particle in the table, the following metal particles are used. For each example, the density of the conductive paste is obtained from the composition of the conductive paste.
[0156] (a) First metal particles: silver-coated particles comprising core particles formed of fused silica and a silver coating layer covering the core particles (silver coating ratio of about 20 mass %, average particle size of 4.1 μm, spherical shape (sphericity: 0.9), aspect ratio of the core particles: about 1, sphericity of the core particles: 0.9)
[0157] (b) Second metal particles: silver particles (aspect ratio: about 3, spherical (sphericity: 0.6), average particle size 2.0 μm)
[0158] (c) Third metal particles: copper particles (average particle size: about 2 μm, sphericity: 0.4)
[0159] It should be noted that the sphericity of each particle corresponds to the sphericity obtained from the cross-sectional image of the metal particle-containing layer according to the above-mentioned procedure.
[0160] (5) Assembly of solid electrolytic capacitors
[0161] In Example 1 and Comparative Example 1, the capacitor element obtained in the above (4) was used to assemble a solid electrolytic capacitor in the following steps.
[0162] The cathode lead layer of the capacitor element is joined to one end of the cathode lead using a conductive adhesive. One end of the portion of the anode body that is not covered by the solid electrolyte layer and the cathode lead layer is joined to one end of the anode lead by laser welding. Then, a resin outer shell formed of an insulating resin is formed around the capacitor element by molding. At this time, the other end of the anode lead and the other end of the cathode lead are formed to be led out of the resin outer shell. In this way, a solid electrolytic capacitor is completed.
[0163] It should be noted that, for the capacitor elements of Examples 1 to 3, the mass ratio of silicon dioxide to silver (metal) in the cross section of the layer containing the first metal particles was calculated according to the above-mentioned steps, and the result was approximately in the range of 0.2 to 3.0. In addition, in the cross section of the layer containing the first metal particles, the area ratio of the first metal particles to the entire metal particles was approximately in the range of 0.50 to 1.00.
[0164] [evaluate]
[0165] The following evaluations were performed using a solid electrolytic capacitor or a capacitor element.
[0166] (a) Leakage current of solid electrolytic capacitor (LC)
[0167] The leakage current (LC) of the solid electrolytic capacitors of Example 1 and Comparative Example 1 was evaluated according to the following procedure.
[0168] A 1 kΩ resistor was connected in series to the solid electrolytic capacitor at 25° C., and a leakage current (μA) was measured after a rated voltage of 2 V was applied for 1 minute using a DC power supply. The average value (initial leakage current (initial LC)) of 30 solid electrolytic capacitors was obtained.
[0169] Next, the solid electrolytic capacitor was allowed to stand at 185°C for 4 hours, and at 85°C in a humidified environment of 85% RH for 12 hours. Next, the solid electrolytic capacitor was allowed to stand at 185°C for 4 hours again, and at 85°C in a humidified environment of 85% RH for 12 hours. Then, assuming a reflow process, the solid electrolytic capacitor was heated at 295°C for 6 minutes. For the leakage current after this heating (reflow), the average value of 30 solid electrolytic capacitors (leakage current after reflow (LC after reflow)) was calculated in the same way as the initial leakage current.
[0170] (b) Short-circuit failure rate of solid electrolytic capacitors
[0171] In the measurement of leakage current after reflow soldering in (a) above, the ratio (%) of the number of solid electrolytic capacitors with leakage current exceeding 1 mA among 30 capacitors was determined. This ratio was defined as the short-circuit defect rate.
[0172] (c)ESR
[0173] The initial ESR (mΩ) of the capacitor elements obtained in Examples 1 to 3 and Comparative Example 1 was measured at a frequency of 100 kHz using a 4-terminal LCR meter at 25° C. Then, the average value of the initial ESR of 40 capacitor elements was obtained.
[0174] The capacitor elements were randomly divided into two groups of 40 each. For one group of capacitor elements, a heat resistance test was performed at 145°C for 450 hours. For the capacitor elements after the heat resistance test, the ESR was measured based on the initial ESR, and the average value of the 40 capacitor elements (ESR after the heat resistance test) was calculated.
[0175] Another group of capacitor elements was subjected to a humidity test at 85°C and 85% RH for 450 hours. The ESR of the capacitor elements after the humidity test was measured based on the initial ESR, and the average value (ESR after the humidity test) of 40 capacitor elements was obtained.
[0176] The evaluation results of the solid electrolytic capacitors are shown in Table 1, and the evaluation results of the capacitor elements are shown in Table 2. In the table, E1 to E3 are Examples 1 to 3, and C1 is Comparative Example 1. It should be noted that the ESR value after the heat resistance test and the humidity resistance test of C1 in Table 2, and the density of the conductive paste are estimated values based on simulation.
[0177] [Table 1]
[0178]
[0179] As shown in Table 1, the initial LC of the solid electrolytic capacitor in E1 using the first metal particles in the cathode and C1 using copper particles hardly changed. In E1, after the solid electrolytic capacitor was exposed to a high temperature and high humidity environment, even after heating with a preset reflow process, the leakage current (LC after reflow) was almost unchanged from the initial LC, and was suppressed to a low level. In addition, in E1, the ratio of solid electrolytic capacitors with a large leakage current exceeding 1mA (LC defect rate) was 0%. For such a result of E1, in C1, the LC after reflow was about 40 times that of E1, and the LC defect rate was also very high, at 36.7%.
[0180] It is believed that the reason why LC increases after reflow soldering in C1 is as follows. It is believed that in C1, when heating is performed in a high-temperature environment and a reflow soldering process is performed, part of the copper particles are ionized and migrate to the solid electrolyte layer, so that the copper component reaches the insulating dielectric layer. It is also believed that the copper component that migrates to the dielectric layer causes current to flow between the anode body and the cathode part, and the leakage current increases.
[0181] In addition, in the first metal particles used in E1, since the core particles are covered with a silver-containing covering layer, the migration of the constituent ions of the first metal particles during the above-mentioned heating under a high temperature environment is suppressed. Moreover, in the case of using the first metal particles, the silver covering layer can ensure high conductivity that is not inferior to the case of using silver particles or silver alloy particles. In addition, the core particles of the first metal particles are silicon dioxide, so compared with silver particles, silver alloy particles or copper particles, etc., the specific gravity is small. Therefore, the cost per unit volume can be suppressed, and the solid electrolyte layer can be covered with a small mass of paste. Therefore, by using the first metal particles, the cost can be reduced, and the leakage current after exposure to high temperature can be reduced, and high reliability can be obtained.
[0182] [Table 2]
[0183]
[0184] As shown in Table 2, in E1, the initial ESR of the capacitor element is significantly lower than that of C1. In the first metal particles used in E1, high conductivity can be ensured by the silver covering layer, and high conductivity of the metal particle-containing layer can be ensured. Therefore, the initial ESR of the capacitor element can be suppressed to a low level. In addition, when the first metal particles and the second metal particles (silver particles, etc.) are used in combination, the specific gravity of the entire metal particles can be suppressed to a certain extent, and the initial ESR (comparison of E1, E2 and E3) can be further suppressed by the high conductivity of the second metal particles. In addition, in E1 to E3 using the first metal particles (and the second metal particles), the oxidative degradation of the metal particles is also suppressed in the heat resistance test and the humidity resistance test, so the ESR of the capacitor element after the heat resistance test or the humidity resistance test can be suppressed to a low level, and high reliability can be obtained.
[0185] It should be noted that, in E2 and E3, the first metal particles and the silver particles as the second metal particles are used in combination, so the migration of the metal components constituting the metal particles such as the copper particles C1 is suppressed. Therefore, in E2 and E3, the same or better leakage current suppression effect as that of E1 in Table 1 can be obtained.
[0186] The present invention has been described with respect to currently preferred embodiments, but such disclosure is not to be construed in a limiting sense. Various modifications and changes should be apparent to those skilled in the art in the art of the present invention upon reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and changes without departing from the spirit and scope of the present invention.
[0187] Industrial Applicability
[0188] The solid electrolytic capacitor disclosed in the present invention can reduce costs and suppress leakage current after exposure to high temperature. The leakage current after reflow soldering can be suppressed to a low level. In addition, in the solid electrolytic capacitor disclosed in the present invention, the initial ESR is low, and the change of ESR can be suppressed after exposure to a high temperature environment or a high temperature and high humidity environment. Therefore, in the present invention, a solid electrolytic capacitor with high reliability can be provided inexpensively. Therefore, the solid electrolytic capacitor can be used for various purposes and is also suitable for purposes requiring high reliability. However, these are simple examples, and the uses of solid electrolytic capacitors are not limited to these examples.
[0189] Description of Reference Numerals
[0190] 1: Solid electrolytic capacitor
[0191] 2: Capacitor element
[0192] 3: Outer shell (resin outer shell)
[0193] 4: Anode lead (anode terminal)
[0194] 5: Cathode lead (cathode terminal)
[0195] 6: Anode
[0196] 7: Dielectric layer
[0197] 8: Cathode
[0198] 9: Solid electrolyte layer
[0199] 10: Cathode lead layer
[0200] 11: First floor
[0201] 12: Second layer
[0202] 13: Separation
[0203] 14: First conductive adhesive layer.
Claims
1. A solid electrolytic capacitor element comprising: an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer, The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer, and at least a portion of the cathode portion includes a metal particle-containing layer, The solid electrolyte layer includes a conductive polymer. The metal particles contained in the metal particle-containing layer include first metal particles containing silver. The first metal particles include: a core particle containing silicon dioxide, and a silver-containing covering layer covering the core particle.
2. The solid electrolytic capacitor element according to claim 1, wherein The first metal particles account for 10 mass % or more of the entire metal particles.
3. The solid electrolytic capacitor element according to claim 1 or 2, wherein: The average aspect ratio of the core particles is 1 or more and 10 or less.
4. The solid electrolytic capacitor element according to any one of claims 1 to 3, wherein The average ratio of the silver-containing coating layer in the first metal particles is 0.1 mass % or more and 50 mass % or less.
5. The solid electrolytic capacitor element according to any one of claims 1 to 4, wherein The metal particles include second metal particles containing silver, The second metal particles are at least one selected from the group consisting of silver particles and silver alloy particles. 6 . A solid electrolytic capacitor comprising: at least one solid electrolytic capacitor element according to claim 1 , and an outer case sealing the solid electrolytic capacitor element. 7 . The solid electrolytic capacitor according to claim 6 , comprising a plurality of the solid electrolytic capacitor elements stacked together.
Citation Information
Patent Citations
Tantalum solid electrolytic capacitor
JP1992085915A